2016
DOI: 10.1123/jpah.2015-0456
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and the Risk of Gallbladder Disease: A Systematic Review and Meta-Analysis of Cohort Studies

Abstract: Background:Physical activity has been hypothesized to reduce the risk of gallbladder disease (gallstones, cholecystitis, cholecystectomy); however, results from epidemiological studies have not always shown statistically significant associations. We conducted a systematic review and meta-analysis to clarify the presence and strength of an association between physical activity and gallbladder disease risk.Methods:PubMed and Embase databases were searched for studies of physical activity and gallbladder disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
14
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 22 publications
5
14
0
3
Order By: Relevance
“…In addition, further studies are needed to clarify which types and intensities of physical activity may be most beneficial for preventing sudden cardiac death. At the population-level physical activity remains an important modifiable risk factor for sudden cardiac death as well as a protective factor for many other diseases including cardiovascular diseases [16,35,36], type 2 diabetes [43], multiple cancers [49], several other diseases [50][51][52][53][54], and premature mortality [55]. Therefore the current results underscore the importance of promoting physical activity for the primary prevention of sudden cardiac death as well as for overall health.…”
Section: Discussionmentioning
confidence: 73%
“…In addition, further studies are needed to clarify which types and intensities of physical activity may be most beneficial for preventing sudden cardiac death. At the population-level physical activity remains an important modifiable risk factor for sudden cardiac death as well as a protective factor for many other diseases including cardiovascular diseases [16,35,36], type 2 diabetes [43], multiple cancers [49], several other diseases [50][51][52][53][54], and premature mortality [55]. Therefore the current results underscore the importance of promoting physical activity for the primary prevention of sudden cardiac death as well as for overall health.…”
Section: Discussionmentioning
confidence: 73%
“…The studies on physical activity and diverticular disease reported the data using different underlying measures (MET-hours per week, or in <3 categories or without quantifying the physical activity level in each category), and for this reason we were not able to conduct dose–response analyses of physical activity. This appears to be a common problem in studies on physical activity and health outcomes [ 34 37 ] and emphasizes the need for a more thorough and standardized approach to analyses and reporting of data on physical activity and different health outcomes. Further studies are therefore needed to characterize the dose–response relationship between physical activity and specific subtypes and intensities of physical activity in relation to diverticular disease, preferably using an underlying metric that could be combined with other published studies, for example using MET-hours per week and/or hours per week of activity.…”
Section: Discussionmentioning
confidence: 99%
“…We also found that prevalences of gallbladder stones and liver steatosis were associated with body size category and metabolic health, even after stratifying for age, gender, and sedentary lifestyle. Gallbladder stones are frequently associated with diabetes [ 40 ], while liver steatosis, apart from being a condition frequently associated with diabetes, is considered to have an important role in promoting atherosclerosis itself [ 41 ]. Insulin resistance, as suggested by corrected HOMA-IR values, was higher in association with both overweight-obesity and MUH condition; a similar trend was also observed for hs-CRP blood concentrations.…”
Section: Discussionmentioning
confidence: 99%